Ancient to medieval : South Indian society in transition - Karashima, Noboru, 1933-2015. (New Delhi : Oxford University Press, 2009)
Collected articles on South Indian history during 12th-14th century.
Includes bibliographical references.
Keywords: Tamil (Indic people) -- Social conditions; India, South -- History